A description of Pseudechiniscus xiai sp. nov., with a key to genus Pseudechiniscus in China - Wang, Lizhi; Xue, Jing; Li, Xiaochen (Zootaxa, 2018)
The new species from the Liupan Mountains in China, Pseudechiniscus xiai sp. nov., differs from other Pseudechiniscus species by the following characters: absence of striae between dots which institute cuticular sculpture, projections absent on caudal margin of pseudosegmental plate, notches absent on caudal margin of terminal plate, dots on ventral side of body forms a reticular patched design. A diagnostic key to the Chinese Pseudechiniscus species is provided.